Otimização do planejamento da operação hidro-energética para o curto prazo - Pedro Henrique Feres Campos (2022)
The hydro power short term planning aims to define the production of hydroelectric plants for the next day in a semi hourly granularity. Due to the limited horizon, the problem must have a detailed model, considering all non linear functions involved and operational restrictions. In this sense, the present work uses a decomposition strategy in order to define a production that's feasible and optimal for each power plant of some cascade. The method considers the main restrictions (including unit commitment), and two main objectives (maximize power and volume), in addition to consider indirectly the desire to produce more power in high load intervals, achieving a power modulation in the final response. Furthermore, besides assertive and detailed, the final response is achieved quickly, allowing the use of the strategy by the energetic programmers as a decision support tool.